2012
DOI: 10.1111/j.1447-0756.2012.01986.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial trisomy of the long arm of chromosome 1: Prenatal diagnosis, clinical evaluation and cytogenetic findings. Case report and review of the literature

Abstract: Partial trisomy of the long arm of chromosome 1 is a relatively rare cytogenetic anomaly. Its phenotype has still not been completely defined, because of the cytogenetic heterogeneity of the cases so far described. We report a prenatal case of partial 1q trisomy associated with partial monosomy 4q, secondary to balanced maternal translocation t(1;4). The trisomic segment extended from 1q31.1 to qter and the monosomy 4q was from 4q35.2 to qter. The phenotypic anomalies found by post-mortem and autopsy examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Cambosu et al observed a prenatal case of duplication of 1q31.1 to qter associated with cerebral ventriculomegaly. Spontaneous abortion was proposed to have occurred due to the chromosomal amplification (Cambosu et al, ). Taysi et al observed trisomy of the long arm of Chromosome 1 in patients manifesting mental retardation and growth malformations (Taysi & Sekhon, ).…”
Section: Discussionmentioning
confidence: 99%
“…Cambosu et al observed a prenatal case of duplication of 1q31.1 to qter associated with cerebral ventriculomegaly. Spontaneous abortion was proposed to have occurred due to the chromosomal amplification (Cambosu et al, ). Taysi et al observed trisomy of the long arm of Chromosome 1 in patients manifesting mental retardation and growth malformations (Taysi & Sekhon, ).…”
Section: Discussionmentioning
confidence: 99%
“…Mothers were healthy Caucasian women who underwent amniocentesis only for advanced age (in Italy, for women aged 35 or over, the category most at risk, the exam is generally recommended) [51,52]. Only samples free of genetic disorders after cytogenetic analysis, performed as described in Cambosu et al [53], were used. The study was performed according to the Declaration of Helsinki.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…AF samples were obtained from pregnant women at the 16th-18th week of gestation and processed at the Genetics and Developmental Biology Unit, AOU Sassari, the reference center for prenatal chromosomal analysis in Northern Sardinia, Italy. The AF was processed as previously reported [53] to obtain AF (cell-depleted). Pellets containing AFCs were suspended in CHANG Medium B Basal supplemented with CHANG Medium C Lyophilized Supplement (Technogenetics S.p.A; Milano, Italy) and 2 mM glutamine, and cultured in a CO 2 incubator at 37 ā€¢ C. The cells were cultured until sub-confluence, then expanded and used at P2 for experiments.…”
Section: Af (Cell-depleted Amniotic Fluid) Preparationmentioning
confidence: 99%
“…Trisomy 1q is reported very rarely in relation to pregnancy and most of the prenatally diagnosed cases are associated with either complete (q11ā€qter) or large (q21ā€qter) duplications with preā€ or perinatal demise of all reported cases. The most common sonographic findings associated with this karyotype abnormality include increased nuchal translucency or nuchal fold, ventriculomegaly, hypoplastic cerebellum, craniofacial dysmorphic features (malformed ears, microstomia, micrognathia, cleft lip/palate), and limb deformities, while renal, cardiac, and gastrointestinal defects are present in some cases (Kaufmann et al, ; Wax et al, ; Pettenati et al, ; Zeng et al, ; Fernandezā€Novoa et al, ; Cambosu et al, ).…”
Section: Introductionmentioning
confidence: 99%